Small RNA pyrosequencing in the protozoan parasite Entamoeba histolytica reveals strain-specific small RNAs that target virulence genes - Zhang, Hanbang (BioMed Central, 2013)
BACKGROUND: Small RNA mediated gene silencing is a well-conserved regulatory pathway. In the parasite Entamoeba histolytica an endogenous RNAi pathway exists, however, the depth and diversity of the small RNA population remains unknown. RESULTS: To characterize the small RNA population that associates with E. histolytica Argonaute-2 (EhAGO2-2), we immunoprecipitated small RNAs that associate with it and performed one full pyrosequencing run. Data analysis revealed new features of the 27nt small RNAs including the 5(′)-G predominance, distinct small RNA distribution patterns on protein coding genes, small RNAs mapping to both introns and exon-exon junctions, and small RNA targeted genes that are clustered particularly in sections of genome duplication. Characterization of genomic loci to which both sense and antisense small RNAs mapped showed that both sets of small RNAs have 5(′)-polyphosphate termini; strand-specific RT-PCR detected transcripts in both directions at these loci suggesting that both transcripts may serve as template for small RNA generation. In order to determine whether small RNA abundance patterns account for strain-specific gene expression profiles of E. histolytica virulent and non-virulent strains, we sequenced small RNAs from a non-virulent strain and found that small RNAs mapped to genes in a manner consistent with their regulation of strain-specific virulence genes. CONCLUSIONS: We provided a full spectrum analysis for E. histolytica AGO2-2 associated 27nt small RNAs. Additionally, comparative analysis of small RNA populations from virulent and non-virulent amebic strains indicates that small RNA populations may regulate virulence genes.